School Physical Education in the pandemic context in the Municipality of Vigia de Nazaré in the state of Pará (Research, Society and Development, 2021)
The present study sought to analyze the implications arising from Remote Learning, in relation to the teaching of the Physical Education curriculum component in times of pandemic by COVID-19. Based on the above, this research aimed to analyze information that would reveal through the reports of Physical Education teachers the reality and challenges faced by them during the pandemic period. An exploratory research with a qualitative approach was used, in which a semi-structured questionnaire was used as an instrument. The research participants were 18 Physical Education teachers who teach in public and private schools in the city of Vigia de Nazaré, Pará State - Brazil. The results revealed the excluding reality of Emergency Remote Education in view of the precarious infrastructure of schools, especially those belonging to rural areas, the fragmented knowledge about the peculiarities and characteristics of Remote Teaching and Hybrid Teaching resulting from a lack of continuing education, which corroborates for the low quality of remote classes. It is concluded that the pandemic caused by COVID-19 also exposed the exclusionary and inefficient panorama of the insertion of educational technologies in the pedagogical action of Physical Education teachers without the proper structuring of schools and adequate training for this.